The Representation of Women in Adult Education Quarterly 1985-2022: A Literature Review - Lisa Baumgartner; Lauren Chaney (Adult Education Research Conference, 2023)
This literature review explores how women are portrayed in Adult Education Quarterly from 1985-2022. Findings indicate increased use of critical frameworks and multiple ways in which women are portrayed.
Keywords: women; literature review; adult education